(untitled) (Architecture Image Studies, 2025)
The current research aims to study the effectiveness and quality of reinforced concrete (ECC) connections when exposed to seismic stresses using ABAQUS software. The study examined and analyzed eight different specimen models with an exact mapping modified Concrete Damaged Plasticity (CDP) model for ECC and validated their representations by comparing them with test results presented in well-established studies in the literature. In summary, there were total improvements in the performance of the ECC reinforced models. For instance, ductility improvements of 40-70%, energy dissipation capacity (up to 55-85%) which implies that the ECC reinforced joints under seismic loading can dissipate more energy upon yielding than their conventional concrete counterparts, and a maximum crack width of ≤ 0.1 mm, compared to 2.5 mm in conventional concrete. This improvement not only increases safety but provides opportunities for a new structural design philosophy in which the design criteria are based on "damage control", rather than simple "collapse prevention"; significantly reducing repair costs from post earthquake inspection and damage or extending the life of the structure. In essence the current work provides a practical-agent validated examples of modeling ECC in modern numerical software along with rational and validated suggestions on how to effectively design with it.